Lumberjanes. True colors - Sturges, Lilah (Lumberjanes, 2020)
At Miss Qiunzella Thiskwin Penniquiqual Thistle Crumpet<U+2019>s Camp for Hardcore Lady-Types, being yourself has a long tradition of being celebrated, and no one knows that better than Ripley, who has spent a summer going where the wind takes her. But sometimes going against the grain is starting to feel like she<U+2019>s going against her friends, and Ripley<U+2019>s not sure if being unique is all it<U+2019>s cracked up to be. So when she meets a Zebracorn with the ability to blend in anywhere, Ripley<U+2019>s starts to think she should take on a new identity, one that looks more like everyone else.